Influence Shift Work on Work Fatigue in Oil and Gas Industry Workers: Literature Review - Rezki Dwinda; Baiduri Widanarko (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: Petroleum and gas industry carries out business in exploration and exploitation activities as well as in the processing of crude oil, an industry that is faced with working conditions and a high level of risk of danger. The work system for workers in the oil and gas sector applies the system shift like shift 4 time rotation, or two week days shift tends to make workers experience higher levels of fatigue and fatigue-related work accidents. For know the influence shift work on work fatigue in oil and gas industry workers. Method: This research uses the method literature review with the PRISMA approach (preferred reporting items for systematic reviews and meta-analyses). In the journal search carried out on database google scholar dan ScienceDirect with the keyword "Shift work”, “Work Fatigue”, “Oil and Gas Industry”. A total of 962 journals were identified, but 5 journals met the inclusion and exclusion criteria. Results: Based on 962 journals identified, 5 journals were selected according to inclusion criteria and exclusion criteria. Work shifts, whether 12-hour rotational work shifts or 2-week rotational shifts for offshore workers, can influence work fatigue in oil and gas workers. Lack of hours of sleep and poor sleep quality and circadian rhythm are often found to be factors causing work fatigue in oil and gas workers. Work fatigue experienced by oil and gas workers has an impact on reducing work performance and work productivity. Conclusion: Shift work has an effect on work fatigue in petroleum and gas industry workers.